Hubungan Kesiapan Diri Terhadap Perubahan Fisik Masa Pubertas Pada Remaja Putri Di SMP Negeri 32 Surabaya - Vivin_Indrianita89 (NERSMID : Jurnal Keperawatan dan Kebidanan, 2019)
Physical changes in adolescence is not a problem that makes it unprepared for everything, but as a teenager who began experiencing various physical changes, of course self-preparation in adolescence is very important for teenagers able to deal with everything bravely. This study aims to determine the relationship of self-preparedness to the physical changes of puberty in young women in Junior Hight Shool at 32 Surabaya. This research uses descriptive method. The sampling technique used is random sampling with a sample of 136 respondents. Data collection using questionnaires to measure Physical changes and Readiness. Technique of data analysis with statistical test of Chi Square got result with significance level α = 0,05 show ρ = 0, 000 means ρ